2018
DOI: 10.9778/cmajo.20180016
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for prevention of vertical HIV transmission in Canada, 1997–2016: a surveillance study

Abstract: Efforts to improve timely access to care, HIV screening and treatment for all women, combined with enhanced resources targeting populations at increased risk for HIV infection, will be needed if vertical HIV transmission is to be eliminated in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…Information on management and health outcomes of pregnant WLWH was abstracted from the CPHSP, a public health surveillance program for vertical transmission of HIV . The CPHSP consists of 22 sites, 19 HIV referral health centres and three health departments from all Canadian provinces and territories.…”
Section: Methodsmentioning
confidence: 99%
“…Information on management and health outcomes of pregnant WLWH was abstracted from the CPHSP, a public health surveillance program for vertical transmission of HIV . The CPHSP consists of 22 sites, 19 HIV referral health centres and three health departments from all Canadian provinces and territories.…”
Section: Methodsmentioning
confidence: 99%
“…Substantial progress has been made with respect to risk reduction of perinatal HIV transmission in Canada. This has been attributed to universal access to antenatal care, routine HIV screening of pregnant women and provision of treatment to those who test positive (16). In 2017, one HIV transmission was confirmed in an infant whose mother was not receiving any perinatal ART and two transmissions were confirmed in infants whose mothers were receiving perinatal ART.…”
Section: Surveillancementioning
confidence: 99%
“…Identification of maternal HIV infection during pregnancy is crucial for timely implementation of antiretroviral prophylaxis, which can both improve the health of the mother and reduce the risk of vertical transmission from 25% (without prophylaxis) to < 5% (Forbes et al 2012;Whitmore et al 2012;Peters et al 2017;Mandelbrot et al 2015;Kimberlin et al 2015;World Health Orgranization (WHO) 2016). A recent national study reported that 14 vertical HIV transmission events occurred between 2011 and 2016 in Canada; however, only five of these pregnant women were diagnosed prior to the onset of labour, indicating that Canadian prenatal care and HIV screening can still be improved (Bitnun et al 2018).…”
Section: Introductionmentioning
confidence: 99%